Pengaruh Komunikasi Antarpribadi Customer Service Terhadap Customer Loyalty Credit Union Bina Seroja - Felicia; Santi Delliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Interpersonal communication is a process carried out by two or more people and carried out directly, such as face to face. This study aims to determine the effect of customer service interpersonal communication on customer loyalty at Credit Union Bina Seroja. The benefits of this research are expected to improve the quality of service provided by customer service Credit Union Bina Seroja. This research uses stimulus-response theory and quantitative methods by distributing questionnaires to 379 respondents to members of Credit Union Bina Seroja and finding out how much satisfaction levels of members of Credit Union Bina Seroja on the services provided by customer service in service. This study indicates an influence of customer service interpersonal communication from five indicators: trust, supportive attitude, open attitude, empathy attitude, and positive attitude. Customer loyalty consists of two indicators, namely making repeat purchases regularly and showing immunity to full competition.